Transcatheter mitral valve‐in‐valve implantation in a pediatric patient. Issue 5 (11th July 2019) - Momenah, Tarek S.; Alsahari, Atif; Ahmed, Eltayeb; Al Khalaf, Khalaf
Abstract: An 11‐year‐old girl, with 25 mm mosaic tissue valve presented with clinical and echocardiographic appearance of stenotic mitral valve prosthesis. Her condition was treated via a transcatheter valve‐in‐valve implantation using a 23 mm Edwards Sapien 3, with satisfactory outcome.